The Dynamics of Formal Islamic Education in Developing Student Character in the Wetu Telu Indigenous Community - Sumiadi, Raden (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study examines the dynamics of formal Islamic education in character development among students in the Wetu Telu indigenous community in Lombok. The Wetu Telu community has a unique belief system and traditions, a blend of Islamic values with deeply rooted animist and Hindu practices. This situation presents unique challenges for formal Islamic educational institutions in instilling Islamic values while respecting the local wisdom that exists within the community. This study uses a qualitative approach with ethnographic methods to explore in depth how schools or madrasahs formulate learning strategies, integrate Islamic religious education curricula, and build harmonious relationships between normative Islamic values and Wetu Telu traditions. The results indicate that formal Islamic education plays a significant role in shaping students' character through a dialogical and accommodative approach, not eliminating local traditions but instead serving as a bridge for internalizing moral values, honesty, responsibility, and religiosity. However, various structural and cultural barriers remain that need to be addressed for the character development process to be optimal and sustainable.